Shipping Law - Baughen, Simon (Routlege, 2019)
In this well-established textbook, Simon Baughen expertly covers the whole spectrum of English shipping law, placing the highly specialised rules of shipping in a commercial context and relating them to the general principles of contract and tort law. The book's accessible narrative and useful glossary of key terms will especially benefit students new to shipping law or from non-law backgrounds.